Reinterpretation and new denomination of Atacisaurus crassiproratus (Middle Eoceneand Issel, France) as cf. Iberosuchus (Crocodylomorpha, Metasuchia) - Ortega, Francisco (1996)
Fil: Ortega, Francisco. Unidad de Paleontología. Departamento de Biología. Universidad Autónoma de Madrid. Madrid; Spain